2021
DOI: 10.33394/jollt.v9i3.3906
|View full text |Cite
|
Sign up to set email alerts
|

When Blended Learning Is Forced in the Amid of Covid-19: What Happen on Efl Learners’ Speaking Anxiety?

Abstract: The existence of Covid-19 has forced the migration of the teaching and learning paradigm from face to face interaction to online learning and to the combination of both known as blended learning. Blended learning is believed to provide opportunity for students to interact with each other with anxiety put at the lowest. This research was aimed to know 1) to what extent is the EFL Learners’ anxiety influenced by blended learning approach in this covid-19 pandemic?; 2) What factors contribute to student’ anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Academic buoyancy predominantly encompasses positive individual-level states, and we recognize the need for a more comprehensive conceptualization of learning presence that considers both positive and negative psychological states. By integrating the assessment of negative psychological traits (Sharma and Sarkar, 2020;Sumarsono et al, 2021), scholars can provide a more nuanced examination of the interrelationships between learning presence and other presences within the Community of Inquiry.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Academic buoyancy predominantly encompasses positive individual-level states, and we recognize the need for a more comprehensive conceptualization of learning presence that considers both positive and negative psychological states. By integrating the assessment of negative psychological traits (Sharma and Sarkar, 2020;Sumarsono et al, 2021), scholars can provide a more nuanced examination of the interrelationships between learning presence and other presences within the Community of Inquiry.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Learners' lack of interest in the lesson also increases the academics' English-speaking anxiety (Sumarsono et al, 2021). A lack of vocabulary is one of the crucial things that make students afraid and worried.…”
Section: Wahyuni (2023)mentioning
confidence: 99%
“…- -------------------------------------------------------------------------------------------------------------------------------------- To help reduce student anxiety, first and foremost, English teachers should be aware of the reality of unease among learners and show empathy to them in class (Sumarsono et al, 2021). Anxiety is one of the most important factors influencing learners' performance in second-language classrooms (Kupchyk & Litvinchuk, 2021).…”
Section: Wahyuni (2023)mentioning
confidence: 99%
“…Of all respondents, female respondents were found to be more anxious than male respondents. Having done the research in Indonesia, Sumarsono et al (2021) found that most EFL students at Mandalika University were anxious when interacting with others using English. The feeling of incompetence, fear of mistake, vocabulary gap, low proficiency, and non-optimal practice was believed to be the triggers of students' anxiety.…”
Section: Introductionmentioning
confidence: 99%